-2(x-3)+3x=42

Simple and best practice solution for -2(x-3)+3x=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-3)+3x=42 equation:


Simplifying
-2(x + -3) + 3x = 42

Reorder the terms:
-2(-3 + x) + 3x = 42
(-3 * -2 + x * -2) + 3x = 42
(6 + -2x) + 3x = 42

Combine like terms: -2x + 3x = 1x
6 + 1x = 42

Solving
6 + 1x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 1x = 42 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 42 + -6
1x = 42 + -6

Combine like terms: 42 + -6 = 36
1x = 36

Divide each side by '1'.
x = 36

Simplifying
x = 36

See similar equations:

| 10sin^2x-7sinx=1 | | 4(x+3.50)=44 | | g(x)=-3x^2+7 | | 13-z= | | E-11=2.9 | | 6cosx+3=0 | | -v^2+30=0 | | -9*cos(2*x)=2 | | 2x+2x+x+x=36 | | 2x^2-6x+9=1 | | 12e^1-15=8 | | w^2+15w-48=0 | | -15x-20=-13x-100 | | 5x=-3y+5 | | x^2-6x-12y-15=0 | | -8p=4-p^2 | | (6y^-2/(6y)^2)^-2 | | 4.3=29.9-4y | | -19.48+x=-2803 | | c/-3-1=2c | | 15.5=-10.1+8w | | y=16x^2+48x+6 | | 27^10*2/3 | | 4(x+1.38)=3x | | lny=lnx+ln(x+13)+lnC | | (8y-1)+(9y-7)= | | 3(c+4)-7=-10c | | 5x+9y=21 | | 6x+7.16=2x+14 | | 1.1=13.9-2x | | 5w+17=(w+1)(w+7) | | (10-4)+3*4+6= |

Equations solver categories